Application Of The Levenshtein String Algorithm In A Web-Based Correspondence System Atbregional Publik Companies (Tirta Hidayah Bengkulu City) - Marhalim Marhalim; Yuza Reswan; Khairullah Khairullah; Achmad Rajes (Jurnal Komputer, Informasi dan Teknologi, 2022)
Management of incoming and outgoing letters at Perumda Tirta Hidayah Bengkulu City involves a lot of paper that must be filled in to record and classify incoming and outgoing letters. By paying attention to this, it is necessary to have a web-based mailing system so that later it can help archiving incoming and outgoing mail and archiving letters can be done effectively and efficiently. The web-based mailing system has been completed using the CodeIgniter 3 framework application and the PHP programming language with MySQL database. The system built can be used at Tirta Hidayah Bengkulu City as a media for processing archival data for incoming and outgoing letters, the system can make it easier for receptionists to enter data, letters, make it easier for leaders (admin secretaries) to carry out the letter disposition process, speed up performance in responding or follow up on incoming mail. The system also produces efficient and accurate mail archive data reports.